Detection of Antibiotic Residues and Mycotoxins in Milk Using Competitive Immunochromatographic Tests - Hriciková S.; Kožárová I.; McGoldrick D.; McCaul O. (Folia Veterinaria, 2023)
As milk should be free from harmful substances before leaving the farm, this study provides the results of the analysis of the presence of β-lactam and tetracycline residues and Aflatoxin M1 (AFM1) in milk samples obtained within one year from Ireland and Slovakia. To evaluate the presence of β-lactam and tetracycline residues, Duplex BT Scan assay, produced by Zeulab S. L. was used. For the detection of AFM1, AflaM1 Scan (Zeulab S. L.) tests were used. Of a total of 69 raw cow’s milk samples analysed, 40 samples were obtained from the farms in Slovakia and 29 samples from the farms in Ireland. Among the 69 analysed samples, 17 (24.6 %) samples were tested positive for the presence of β-lactam residues, 12 (17.4 %) samples for tetracycline residues and 59 (88.4 %) samples for AFM1. Milk samples positive for antibiotic residues and mycotoxins were not acceptable and it is important that the reputation of milk as a healthy and safe food is protected worldwide. Dairy farmers and consumers want to be confident that milk and milk products are of high quality and free of all pharmacologically active substances and toxins.